Neurologic Complications of Infective Endocarditis: A Joint Model for a Septic Thromboembolism and Inflammatory Small Vessel Disease. Issue 8 (August 2019) - Cantier, Marie; Sabben, Candice; Adle-Biassette, Homa; Louedec, Liliane; Delbosc, Sandrine; Desilles, Jean-Philippe; Journé, Clément; Diallo, Devy; Ou, Phalla; Klein, Isabelle; Chau, Françoise; Lefort, Agnès; et al.
Abstract : Objectives: Embolic events from vegetations are commonly accepted as the main mechanism involved in neurologic complications of infective endocarditis. The pathophysiology may imply other phenomena, including vasculitis. We aimed to define the cerebral lesion spectrum in an infective endocarditis rat model. Design: Experimental model of Staphylococcus aureus or Enterococcus faecalis infective endocarditis. Neurologic lesions observed in the infective endocarditis model were compared with three other conditions, namely bacteremia, nonbacterial thrombotic endocarditis, and healthy controls. Setting: Research laboratory of a university hospital. Subjects: Male Wistar rats. Interventions: Brain MRI, neuropathology, immunohistochemistry for astrocyte and microglia, and bacterial studies on brain tissue were used to characterize neurologic lesions. Measurements and Main Results: In the infective endocarditis group, MRI revealed at least one cerebral lesion in 12 of 23 rats (52%), including brain infarctions ( n = 9/23, 39%) and cerebral microbleeds ( n = 8/23, 35%). In the infective endocarditis group, neuropathology revealed brain infarctions ( n = 12/23, 52%), microhemorrhages ( n = 10/23, 44%), and inflammatory processes (i.e., cell infiltrates including abscesses, vasculitis, meningoencephalitis, and/or ependymitis; n = 11/23, 48%). In the bacteremia group, MRI studies were normal and neuropathology revealed only hemorrhages ( n = 2/11, 18%). Neuropathologic patterns observed in the nonbacterial thrombotic endocarditis group were similar to those observed in the infective endocarditis group. Immunochemistry revealed higher microglial activation in the infective endocarditis group ( n = 11/23, 48%), when compared with the bacteremia ( n = 1/11, 9%; p = 0.03) and nonbacterial thrombotic endocarditis groups ( n = 0/7, 0%; p = 0.02). Conclusions: This original model of infective endocarditis recapitulates the neurologic lesion spectrum observed in humans and suggests synergistic mechanisms involved, including thromboembolism and cerebral vasculitis, promoted by a systemic bacteremia-mediated inflammation. Abstract : Supplemental Digital Content is available in the text.